Physicochemical characterization of two bulk fill composites at different depths - Guillermo Grazioli; Carlos Enrique Cuevas-Suárez; Leina Nakanishi; Alejandro Francia; Rafael Ratto de Moraes (Restorative Dentistry & Endodontics)
ObjectivesThis study analyzed the physical-chemical behavior of 2 bulk fill resin composites (BFCs; Filtek Bulk Fill [FBF], and Tetric-N-Ceram Bulk Fill [TBF]) used in 2- and 4-mm increments and compared them with a conventional resin composite (Filtek Z250).Materials and MethodsFlexural strength and elastic modulus were evaluated by using a 3-point bending test. Knoop hardness was measured at depth areas 0–1, 1–2, 2–3, and 3–4 mm. The translucency parameter was measured using an optical spectrophotometer. Real-time polymerization kinetics was analyzed using Fourier transform infrared spectroscopy.ResultsFlexural strength was similar among the materials, while TBF showed lower elastic modulus (Z250: 6.6 ± 1.3, FBF: 6.4 ± 0.9, TBF: 4.3 ± 1.3). The hardness of Z250 was similar only between 0–1 mm and 1–2 mm. Both BFCs had similar hardness until 2–3 mm, and showed significant decreases at 3–4 mm (FBF: 33.45 ± 1.95 at 0–1 mm to 23.19 ± 4.32 at 3–4 mm, TBF: 23.17 ± 2.51 at 0–1 mm to 15.11 ± 1.94 at 3–4 mm). The BFCs showed higher translucency than Z250. The polymerization kinetics of all the materials were similar at 2-mm increments. At 4-mm, only TBF had a similar degree of conversion compared with 2 mm.ConclusionsThe BFCs tested had similar performance compared to the conventional composite when used in up to 2-mm increments. When the increment was thicker, the BFCs were properly polymerized only up to 3 mm.